Operating and Planning Electricity Grids with Variable Renewable Generation : Review of Emerging Lessons from Selected Operational Experiences and Desktop Studies - Madrigal, Marcelino; Porter, Kevin (Washington, DC: World Bank, 2013)
The development of wind-and solar-generating capacity is growing rapidly around the world as policy makers pursue various energy policy objectives. This paper will describe the challenges in integrating wind and solar generation, the lessons learned, and recommended strategies from both operating experience and integration studies. Case studies on the experience with wind and solar integration in China, Germany, and Spain are also included in this paper. The paper is organized as follows. First section summarizes worldwide wind and solar development, the challenges in integrating wind and solar generation, and some of the lessons learned from studies designed to evaluate the impact of higher levels of wind and solar generation and also from the operational experience in some countries with larger amounts of renewable energy. The second section summarizes some of the solutions for incorporating higher levels of wind and solar capacity into short-term system operations. This section also explains basic methodologies to implement system operations studies to understand the impacts of variability in system operation. The third section explains the contribution of variable renewables to long-term supply adequacy-commonly called 'firm' power-and the relationship of this to long-term reserves; it also explores how these issues can be incorporated into long-term planning or adequacy assessments. Overall, the variability of wind power generation adds to the variability on the grid in most time scales, and a key question that wind integration studies must address is whether there is enough existing capability on the grid to manage that increased variability, or whether new sources, such as new generation or increased levels of demand response, must be added to manage that variability.